La novel·la històrica en mans de Josep Lozano: Crim de Germania i El Mut de la Campana. - Francés, M. Jesús (Scripta, 2019)
Any analysis about Josep Lozano's historical novels is undoubtedly associated to his prestigious work Crim de Germania, which the Ribera born author released in 1980. Some 20 years later he created another historical novel, El Mut de la Campana (2003), once again showing his mastery of the genre. The purpose and structure of both works are different, but what motivated the author to use such a creative format in the 80's persists today: travel back in time, and tell the story as if it were the modern day through a fictional filter and, in doing so, showing what Valencian society was like. A society, this one, which is prevalent throughout both works, shows how it works collectively as well as how it is defined by its idiosyncrasies.